The context dependence of frontier versus wilderness conservation priorities. Issue 3 (7th February 2019) - Sacre, Edmond; Bode, Michael; Weeks, Rebecca; Pressey, Robert L.
Abstract: Much of conservation planning has focused on how we should prioritize areas for protection based on biodiversity and cost, but less is known about how we should prioritize areas based upon the level of threat they face. We discuss two opposing threat prioritization strategies: frontier conservation (prioritizing high‐threat areas) and wilderness conservation (prioritizing low‐threat areas). Using a temporally explicit model, we demonstrate that the best strategy depends on a variety of factors, including protection costs, heterogeneity in biodiversity, biodiversity–area relationships, the rate of biodiversity recovery, the rate of change in threats through time, and the timeframe within which we measure conservation outcomes. By quantitatively comparing the impact of these strategies, we aim to shift the debate away from a simple dichotomy of frontier versus wilderness, toward an understanding of the context‐specific benefits of each option, and a discussion of how threat combines with other factors to determine spatial conservation priorities.